Serum p53 antibodies detection in oral squamous cell carcinoma, oral potentially malignant disorders and healthy indiviuals – a multicentre study - Saleem Khan, Abbas; Sajjad Ahmad; Zahoor Ullah; Mohsina Haq; Muhammad Umar Farooq; Muslim Khan (Journal of the Pakistan Medical Association, 2021)
Objective: To detect antibodies against p53 in serum of patients of oral squamous cell carcinoma and oral potentially malignant disorders compared to healthy individuals. Method: The descriptive cross-sectional study was conducted at the departments of Oral and Maxillofacial Surgery, Peshawar Dental College, Peshawar, Khyber College of Dentistry, Peshawar, and the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from April2016 to March2017, and comprised serum of oral squamous cell carcinoma patients in group A, oral potentially malignant disorder patients in group B and healthy individuals in group C. Serum concentrations of anti-p53 antibodies were determined by enzyme-linked immunosorbent assay. Data was analysed using SPSS 20. Results: Of the180 subjects, there were 60(33.3%) in each of the three groups. Circulating serum p53 antibodies were detected in 59(98.3%) cases in group A, 58(96.6%) in group B and in 20(33.3%) individuals in group C (p=0.001). Conclusion: The expression of circulating p53 antibodies in serum samples of squamous cell carcinoma and oral potentially malignant disorders patients indicates the potential to be a probable candidate for being taken as a diagnostic or prognostic biomarker. Key Words: Tumour suppressor genes, TSGs, Oral squamous cell carcinoma, OSCC, Oral potentially malignant disorders, OPMDs, p53, ELISA. Continuous...